Perubahan Karaktersik Lahan Di Kawasan Strategis Kasiba-Lisiba Talang Kelapa Kota Palembang - S., Asninda Krisnamutri; Marsoyo, Agam; Pramono, R. Widodo Dwi (Fakultas Teknik, Universitas Brawijaya, 2018)
Kasiba-Lisiba is a strategic area with comparative advantages based on settlements. The government of Palembang City has established Kasiba-Lisiba as a strategic area as an effort to make distribution and development of settlements. As a driving force in the regional development, the impact of settlements as a growth center has not been widely known. Identify the effect of the determination can be shown on the change of land characteristics.The purpose of this study is to identify changes in land characteristics before and after the establishment of strategic areas in Kasiba-Lisiba Palembang City. The method used in this research is a quantitative-qualitative deductive method (mix method). The analysis used quantitative descriptive analysis, before-after analysis, and cross tabulation analysis. The result of the analysis shows that based on five land characteristic variables, there are four variables that have changed namely: built-up area, land price, land title, and land utilization, while one attribute of land that is not changed between before and after Kasiba-Lisiba determination is land tenure. With the establishment of Kasiba-Lisiba Talang Kelapa as a fast-growing area has a significant influence or relationship to the changing land characteristics in the area.Keywords: land characteristic, kasiba-lisiba, growth pole